2013
DOI: 10.1186/1745-6215-14-84
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin, pyuria and proadrenomedullin in the management of urinary tract infections – ‘triple p in uti’: study protocol for a randomized controlled trial

Abstract: BackgroundUrinary tract infections (UTIs) are among the most common infectious diseases and drivers of antibiotic use and in-hospital days. A reduction of antibiotic use potentially lowers the risk of antibiotic resistance. An early and adequate risk assessment combining medical, biopsychosocial and functional risk scores has the potential to optimize site-of-care decisions and thus allocation of limited health-care resources. The aim of this factorial design study is twofold: first, for Intervention A, it inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…One additional publication was obtained through contact with the authors, 69 after searches had identified the study protocol. 47 Figure 1 shows the flow of studies through the review process, and Appendix 4 provides details, with reasons for exclusions, of all publications excluded at the full paper screening stage.…”
Section: Results Of the Assessment Of Clinical Effectiveness Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One additional publication was obtained through contact with the authors, 69 after searches had identified the study protocol. 47 Figure 1 shows the flow of studies through the review process, and Appendix 4 provides details, with reasons for exclusions, of all publications excluded at the full paper screening stage.…”
Section: Results Of the Assessment Of Clinical Effectiveness Assessmentmentioning
confidence: 99%
“…Ten RCTs, 39,42,44,49,[55][56][57]60,62,69 reported in 16 publications, 39,40,[42][43][44][47][48][49][55][56][57][58][59]62,69,70 provided data on the effectiveness of adding PCT testing to the information used to guide antibiotic therapy in ED settings. Two studies 39,49 were conducted in children, and the remainder 42,44,[55][56][57]60,62,69 were conducted in all adult populations.…”
Section: Study Detailsmentioning
confidence: 99%
“…We show the development, implementation and use of the algorithm with proadrenomedullin enhanced CURB65 score over four years in our publications. The description of the derivation of the biomarker enhanced score, clinical trial, and post-study surveillance could be used as a model for new clinical scores and algorithms in LRTI and other diagnosis [ 24 , 25 ]. The studies (OPTIMA I–III) had well characterized cohorts, similar methodology and overall 341 patients with radiologically confirmed CAP.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we focus on the efficacy of an algorithm based on clinical symptoms, PCT, and pyuria to safely reduce the duration of antibiotic therapy compared to current guidelines [ 6 , 15 , 28 ]. Details of the full trial design and methods have been published elsewhere [ 29 ].…”
Section: Methodsmentioning
confidence: 99%